Student Empathy Attitude in Supporting Competence as a Prospective Counselor - Hasan Bastomi (Islamic Counseling : Jurnal Bimbingan dan Konseling Islam, 2021)
This study aims to determine the quality of the empathy attitude of the Islamic Education Counseling Guidance students of IAIN Kudus in Supporting Competence as a Prospective Counselor. This research uses qualitative methods with the type of field research (field research), data mining using questionnaires, observation, interviews and documentation then analyzed using a percentage descriptive table. The results showed that the empathy attitude of the students of Islamic Education Counseling Guidance was in the good category, namely 58%. Although it is still regarded as unsatisfactory, it is a fundamental skill of the counselor. However, it is said that counseling students can develop their empathy better than students in other fields, such as medicine, nursing, and students in the social work field. Suggestions as Guidance and Counseling students are necessary to develop an obedient attitude both through lecture learning and in other forms of activity.